Um panorama sobre as tecnologias assistivas nas redes de ensino de Santarém-Pa através dos microdados do censo escolar/INEP - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2019)
In recent years there has been a growing number of people with disabilities (PCD) in the classroom. This increase has been due to the implementation of decrees establishing guidelines aimed at guaranteeing access and permanence of students with special educational needs in school and establishing Specialized Educational Attendance (ESA) at the educational levels. One of the tools used to include students with special educational needs is computers. These should be used to facilitate learning through software, with the help of a specialized teacher. Given this, this paper seeks to present an overview regarding the inclusion of assistive technology services in accessible informatics for the care of students with disabilities, associated or not with visual and cognitive sensory impairment, physical disability and multiple disabilities in the schools of the state. municipality of Santarém. The collected data were obtained through the School Census microdata from 2011 to 2018. It aims to make this information recognized by the local inclusive society, about the fact of its population. As preliminary results, we present in this paper a historical series about the number of PCDs in urban and rural schools, the types of disabilities, the conditions existing in the schools regarding the adequacy of spaces, besides the teaching series. Considering the results obtained, it was observed that with the development of inclusive education policies, there is a growing evolution regarding the enrollment of PCDs in schools, however, with no necessary adaptation yet for the teaching to the students. Due to the amount of information available on the subject, this work also highlights other results that include schools and teachers.
Keywords: Educação; Tecnologia Assistiva; Computadores; Informática Inclusão; CNPQ:: CIÊNCIAS EXATAS E DA TERRA